If you can keep it : the forgotten promise of American liberty - Metaxas, Eric (Viking, 2016)
Eric Metaxas offers a thrilling review of America's uniqueness, and a sobering reminder that America's greatness cannot continue unless people truly understand what their founding fathers meant for them to be. The book includes a stirring call-to-action for every American to understand the ideals behind the 'noble experiment in ordered liberty' that is America. It also paints a vivid picture of the tremendous fragility of that experiment and explains why that fragility has been dangerously forgotten - and in doing so it lays out our own responsibility to live those ideals and carry on those freedoms. Metaxas believes America is not a nation bounded by ethnic identity or geography, but rather by a radical and unprecedented idea, based upon liberty and freedom.